Tinjauan Hukum Persaingan atas Penunjukan Langsung dalam Sinergi BUMN Berdasarkan PER-2/MBU/2023 - Vanya Amanda Filza Yunas (Pusat Riset dan Inovasi Nasional, 2025)
.SOE Synergy policy has drawn significant attention over the years due to its potential to create conflicts with the principles of fair competition. However, the provision still remains, particularly regarding direct appointment as stipulated in Article 155 paragraph (2) letter j of the Minister of SOE Regulation Number PER-2/MBU/3/2023 concerning Guidelines for Governance and Significant Corporate Activities of SOEs. This doctrinal research, presented descriptively based on secondary data obtained through a literature review of various legal materials, aims to examine the perspective of competition law on the SOE Synergy policy in the context of direct appointment as stated in the aforementioned regulation. Specifically, this research seeks to analyze whether the provisions on direct procurement in the regulation comply with the provisions of Law Number 5 of 1999 concerning the Prohibition of Monopolistic Practices and Unfair Business Competition. The findings suggest that the direct appointment provisions in Article 155 paragraph (2) letter j of the regulation may create barriers to entry for other businesses and potentially stifle fair competition. The regulation on SOEs Synergy should be complemented by more detailed provisions on the implementation mechanism to ensure that the objectives of the policy can be achieved efficiently while maintaining a fair competition. Furthermore, a thorough cooperation between the Ministry of SOE and the Competition Commission is needed to ensure its adherence to the principles of fair competition.